The Psychometric Properties of the Norwegian version of Child Outcome Rating Scale(CORS) - Kornør, Hege; Hanssen-Bauer, Ketil (PsykTestBarn, 2014)
Description: CORS was originally developed in the USA in 2003 by Duncan, Miller and Sparks to measure self-reported outcomes of therapy. The Norwegian version was translated by Anne-Grethe Tuseth, and is available online. CORS contains four visual analog scales that children aged 6-12 years and/or their caregivers rate by marking where the child is on a line with a sad face in one end and a happy face in the other end. Administration and scoring takes few minutes and there are no requirements to test user qualifications. Literature search: Our systematic literature searchfor evidence for the psychometric properties of the Scandinavian versions of CORS identified no relevant publications. Conclusion: No evidence for the psychometric properties of the Norwegian version of CORS is available. There is therefore a need for psychometric studies.